Efektivitas Pemberian Kompres Daun Sirih terhadap Percepatan Penyembuhan Luka Perineum di PMB Lina Contesa - Devina Anggrainy Dencik (Pusat Riset dan Inovasi Nasional, 2026)
Perineal wounds are common among postpartum women and can interfere with recovery if not properly treated. One non-pharmacological approach to accelerate wound healing is the use of betel leaf (Piper betle L.) compresses, which possess antiseptic, anti-inflammatory, and astringent properties. This study aimed to determine the effectiveness of betel leaf compresses in accelerating perineal wound healing among postpartum women at PMB Lina Contesa. This research employed a quasi-experimental design with a pretest-posttest control group approach involving 32 respondents divided into intervention and control groups. The instrument used was an observation sheet assessing perineal wound healing. The Wilcoxon test results showed a significant improvement in wound healing scores in the intervention group (p = 0.000), while no significant difference was found in the control group (p = 0.083). The Mann-Whitney test indicated a significant difference between the two groups (p = 0.001). It can be concluded that betel leaf compresses are effective in accelerating perineal wound healing among postpartum women. The findings of this study are expected to serve as a basis for implementing herbal-based care as a complementary therapy in midwifery practice.